Passing of Risk in Convention on the International Sale of Goods - Ay, Yunus Emre (Teisė, 2021)
Passing of risk is an indispensable issue of contract of sale transactions. It determines which party bears the loss or damage of goods. This issue is more important in international commercial transactions than in national contract of sale transactions. Therefore, CISG lays down rules on passing of risk. CISG Articles 66–70 regulate passing of risk provisions. The purpose of this paper is to analyse CISG Articles 66–70.